Family Acceptance of Social Stigma and Caregiving Burden in Schizophrenia: Hubungan Penerimaan Keluarga Terhadap Stigma Masyarakat Dan Beban Perawatan Skizofrenia - Rina Dwi Rahman; Edy Soesanto; Sri Karyati (Academia Open, 2026)
General Background Schizophrenia is a severe mental disorder that imposes considerable psychological and social demands on patients and their families within community-based care. Specific Background Families caring for individuals with schizophrenia often experience social stigma, which may affect family acceptance and contribute to caregiving burden. Knowledge Gap Evidence examining the relationship between family acceptance of social stigma and caregiving burden in primary health care settings remains limited. Aims This study aimed to analyze the relationship between family acceptance of social stigma and family caregiving burden among schizophrenia caregivers in the working area of Kragan II Community Health Center, Rembang Regency. Results A descriptive correlational study with a cross-sectional design involving 80 family caregivers showed a significant association between family acceptance of social stigma and caregiving burden (p = 0.027), indicating that higher acceptance was associated with lower perceived burden. Novelty This study offers context-specific evidence from a primary health care setting by emphasizing family experiences of social stigma in schizophrenia caregiving. Implications The findings highlight the importance of integrating family-centered mental health services, including education and caregiver support, within primary health care to address stigma-related challenges and reduce family caregiving burden. Highlights: Family acceptance of social stigma is significantly associated with caregiving burden Lower perceived burden is observed among families with better stigma acceptance Primary health care settings play a key role in supporting schizophrenia caregivers Keywords: Family Acceptance; Social Stigma; Family Burden; Schizophrenia; Primary Health Care Published date: 2026-02-10